2018
DOI: 10.4274/balkanmedj.2017.0888
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Dilemma for Low Viremia with Significant Fibrosis; is Hepatitis B Virus DNA Threshold Level a Good Indicator for Predicting Liver Damage?

Abstract: Background:The most important difficulties about management of hepatitis B are still determining the liver damage and the right time to start antiviral therapy.Aims:To reveal the role of hepatitis B virus DNA threshold level for prediction of liver fibrosis and inflammation in young-aged hepatitis B e-antigen negative chronic hepatitis B patients.Study Design:Diagnostic accuracy study.Methods:A total of 273 hepatitis B e-antigen negative young chronic hepatitis B patients with any hepatitis B virus DNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…It is argued to decrease the ALT threshold levels as 19-25 U/L for females and 30-33 U/L for males in the WHO and AASLD guidelines, and the latest AASLD guideline support the ALT threshold levels as 25 U/L for females and 35 U/L for males in the management procedure of chronic HBV. On the contrary, APASL and EASL accept that there are no available data to support the need for lowering the traditional thresholds for the ULN of ALT values 6. And also in literature, ALT levels between 25 and 40 U/L is considered as high normal, in which histopathological changes is more likely to occur 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is argued to decrease the ALT threshold levels as 19-25 U/L for females and 30-33 U/L for males in the WHO and AASLD guidelines, and the latest AASLD guideline support the ALT threshold levels as 25 U/L for females and 35 U/L for males in the management procedure of chronic HBV. On the contrary, APASL and EASL accept that there are no available data to support the need for lowering the traditional thresholds for the ULN of ALT values 6. And also in literature, ALT levels between 25 and 40 U/L is considered as high normal, in which histopathological changes is more likely to occur 7…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are few studies in HBeAg-positive cases aiming on correlation or relationship between HBV-DNA and liver fibrosis and/or necroinflammation; studies are mostly in HBeAg-negative cases 6,16-19. Hepatitis B virus-DNA threshold level for the treatment indication of CHB due to the reimbursement arrangements of Turkey is 2,000 IU/mL; same level for both HBeAg-positive and negative CHB cases 13.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Deng et al 14 reported disease progression in those with low HBV DNA loads. Yenilmez et al 19 also found that the risk of liver fibrosis cannot be ignored in CHB patients with low viral loads. In brief, the risk of disease progression exists as long as we can detect virus replication with an available assay, which is equivalent to an antiviral therapy indication.…”
Section: Precise Hbv Dna Load Provides Guidance For Antiviral Therapymentioning
confidence: 99%
“…For patients with liver cirrhosis, the risk of HBV DNA levels not reaching 2000 IU/mL is still very high ( 58 ). However, current studies indicate that low-level viremia can also cause HCC ( 59 ). Low-level viremia (LLV) is defined as a level of HBV DNA continuously or intermittently greater than the detection limit but less than 2000 IU/mL.…”
Section: Risk Predictionmentioning
confidence: 99%